Experimental validation of quasi-one-dimensional and two-dimensional steady glottal flow models - Cisonni, Julien; Van Hirtum, A.; Luo, X.; Pelorson, X. (Springer, 2010)
Physical modelling of phonation requires a mechanical description of the vocal fold coupled to a description of the flow within the glottis. In this study, an in-vitro set-up, allowing to reproduce flow conditions comparable to those of human glottal flow is used to systematically verify and discuss the relevance of the pressure and flow-rate predictions of several laminar flow models. The obtained results show that all the considered flow models underestimate the measured flow-rates and that flow-rates predicted with the one-dimensional model are most accurate. On the contrary, flow models based on boundary-layer theory and on the two-dimensional numerical resolution of Navier-Stokes equations yield most accurate pressure predictions. The influence of flow separation on the predictions is discussed since these two models can estimate relevant flow separation positions whereas this phenomenon is treated in a simplified ad-hoc way in the one-dimensional flow modelling. Laminar flow models appear to be unsuitable to describe the flow downstream of the glottal constriction. Therefore, the use of flow models taking into account three-dimensional effects as well as turbulence is motivated. © 2010 International Federation for Medical and Biological Engineering.